Investigating the effects of autonomy-supportive parenting practices on Italian young adolescent students’ motivation to defend victims of bullying: findings on the mediating roles of reactance, depression, anxiety, and stress - Iotti, Nathaniel Oliver; Menin, Damiano; Longobardi, Claudio; Jungert, Tomas (Frontiers in Psychology, 2023)
This study investigated the effect of autonomy-supportive parenting practices on young adolescents’ self-reported motivation to defend victims of bullying, and the possible mediating effects of factors such as reactance, anxiety, depression, and stress. Methods Data were collected from 578 Italian public school students ages 10–14 (Mage = 11.8 years, 52% boys), who completed a survey in their classroom. The survey included self-report measures of parental orientation, motivation to defend victims of bullying, reactance, anxiety, depression, and stress. Results We found that autonomy-supportive parenting had a positive effect on autonomous motivation to defend, and that this effect was weakly mediated by reactance. Moreover, autonomy-supportive parenting had a negative effect on extrinsic motivation to defend, which was partially mediated by reactance. Reactance had a positive direct effect on extrinsic motivation to defend, but results also showed that anxiety, depression, and stress did not mediate the effect of autonomy-supportive parenting on motivation to defend. Additionally, autonomy-supportive parenting appeared to play a protective role, being associated with lower levels of reactance, anxiety, depression, and stress. Finally, gender differences were found in our sample, with extrinsic motivation to defend being more prevalent in boys, and autonomous motivation to defend being more prevalent in girls. Girls also reported higher levels of anxiety, depression, and stress, compared to boys. Conclusion Our findings show that autonomy-supportive parenting practices play a significant role in fostering young adolescents’ motivation to defend victims of bullying, and that they are also linked with lower feelings of reactance, anxiety, depression, and stress. We argue that interventions aimed at contrasting bullying and cyberbullying among youths should seek to involve parents more and promote the adoption of more autonomy-supportive parenting practices, due to their consistently proven beneficial effects.